Counseling on Improving the Quality of Life for the Elderly Through the Implementation of Healthy Lifestyles in the Land of Java, Simalungun - Friani, Sri Rahma; Ma’ruf, Ibnu Jafar; Peranginangin, Winda Melisa; Sinambela, Masna Maria (International Journal of Community Service (IJCS), 2024)
This research is a real action Counseling on Improving the Quality of Life of the Elderly Through the Implementation of Healthy Lifestyles in the Land of Java Simalungun. Old age is a time when people will eventually experience it. Many people can enjoy old age, but few experience illness and die without being able to enjoy old age happily. Everyone certainly wants to have a happy old age, but wishes cannot always be realized. In real life, many elderly people become depressed, stressed and suffer from chronic diseases. A study program-based community service activity has been carried out by the Undergraduate Nursing Study Program, Faculty of Public Health, Efarina University. A partner village is Nagari Sumaniak, Simalungun Regency, which is a village fostered by Andalas University. The service activity is entitled Improving the Quality of Life of the Elderly Through the Implementation of Healthy Lifestyles in Tanah Jawa, Simalungun Regency in 2020. The service activity was carried out for two days. The first day's activity was mutual cooperation in creating a medicinal plant garden in the yard of the elderly posyandu by the Undergraduate Nursing Study Program students. The second day's activities included the distribution of tensiometers, the distribution of elderly pocket books, and elderly health education regarding meeting the elderly's nutritional needs and physical activity